Inheritance of seed protein content and other agronomic characters in long bean (Vigna sesquipedalis Fruw.) - Mak, C.; Yap, T. C. (Springer-Verlag, 1980)
Seven varieties of long bean, which included three local and four exotic, were crossed in a complete diallel. This was an attempt to study the inheritance of crude protein content, protein yield, flowering date, pod yield and yield components. Both additive and non-additive gene effects were responsible for the genetic variation in the diallel population. However, dominance variance was more important than additive variance in crude protein content, number of pods per plant and number of seeds per pod. For seed weight and pod length, additive variance was more important. The crude protein content, protein yield and number of pods per plant appeared to be controlled by overdominance effects. Partial dominance seemed to be the case for flowering date, pod length and seed weight; complete to overdominance for pod yield. High protein appeared to be associated with recessive genes whereas there was a general trend of high yielding parents carrying more dominant genes. © 1980 Springer-Verlag.